PERSEPSI VISUAL ANAK MUDA BANDAR LAMPUNG TERHADAP MOTIF KHAS LAMPUNG (PUCUK REBUNG DAN KAPAL) - Muhammad Hajid An Nur; Susi Susyanti; Arif Budiman (LPPM Institut Bisnis dan Teknologi Indonesia, 2019)
Lampung has many traditional and distinct motifs, one of which is â€œPucuk Rebungâ€ and â€œKapalâ€. Both of these motifs are visual elements that we can find on Lampung's weaving, Tapis. As time goes by, these traditional motifs had undergone a shift in terms of production technique, application, and public perception of the motifs. This traditional motif has been developed by creative industries such as several distro in Lampung and applied to fashion products, ranging from accessories, t-shirts, and so on. Research shows a change in traditional motifs (Pucuk Rebung and Kapal), especially on composition and application of motifs, and not on the main visual elements itself. This certainly shifts the visual perceptions of Lampung youth towards the traditional motifs. Research on Lampung youths visual perceptions of traditional motifs will help designers to innovate, especially in utilizing Lampung's distinctive motifs. Research shows that traditional motifs score slightly higher than the new motifs. traditional motifs (both Pucuk Rebung and Kapal) are considered more dynamic, more elegant, (giving) more (sense of) proud, more meaningful, and better.